Back Cover: Quantitative proteomic profiling of paired cancerous and normal colon epithelial cells isolated freshly from colorectal cancer patients. Issue 5 (4th May 2017) - Tu, Chengjian; Mojica, Wilfrido; Straubinger, Robert M.; Li, Jun; Shen, Shichen; Qu, Miao; Nie, Lei; Roberts, Rick; An, Bo; Qu, Jun
Abstract : DOI:10.1002/prca.201600155 Though widely practiced, proteomic comparison of tumors vs. normal tissues may not yield accurate biological/clinical information because of the heterogeneous tissue compositions. Here the authors address this problem by comparing antibody‐isolated, viable cancerous(CEC) vs. normal(NEC) epithelial cells from tumor and normal regions from CRC patients. An IonStar MS1 strategy achieved reliable comparison of N=120 samples; novel candidates of biomarkers and therapeutic targets, as well as new insights into disease mechanisms, were revealed. This is reported by Chengjian Tu et al., article number 1600155.